(untitled) (World Economics and Finance Bulletin, 2026)
The global audit profession faces mounting pressure to deliver consistently high-quality audit engagements amid complex business environments, increasing regulatory scrutiny, and evolving stakeholder expectations. International Standards on Auditing (ISAs), issued by the International Auditing and Assurance Standards Board (IAASB), constitute the foundational framework for enhancing audit quality worldwide